Process optimisation: spinal versus general anaesthesia for endourological surgery. A randomised, controlled trial and machine-learning approach. - Skitek, Kornel; Schittek, Gregor A.; Soukup, Jens (Anaesthesiology Intensive Therapy / Anestezjologia, Intensywna Terapia, 2024)
Background: Data concerning anaesthesia for endourology are rare, and options for it are numerous. Thus, identifying the optimal anaesthesia regimen remains challenging. With this study we aimed to provide the means for selecting optimal anaesthesia for endourology procedures. Methods: This was a randomised, open-label, controlled study conducted in a single tertiary hospital. Inclusion criteria: American Society of Anesthesiologists (ASA) physical status/risk category I–III, and scheduled surgery time < 60 minutes. Exclusion criteria: contraindications or lack of consent for one of the anaesthesia types, intellectual disabilities, pregnancy, breastfeeding, and refusal to participate. The participants were divided into 3 groups: G1, spinal anaesthesia (SPA) with bupivacaine; G2, SPA with prilocaine; G3, total intravenous anaesthesia (TIVA) with remifentanil and propofol. The primary outcome measure was time to ambulation, while the secondary outcome measures included perioperative hypotension. The results are presented as mean ± SD or median [IQR]. Results: In total, 117 patients completed the study. The time to ambulation (minutes) was significantly different between all groups: 187.95 ± 49.82, 161.05 ± 46.28, and 129.14 ± 63.75 min, for G1, G2 and G3, respectively. The mean arterial pressure drop from baseline during the procedure was most pronounced in G3 (35% [30–44], P < 0.001) and lowest in G2 (18% [12–27], P < 0.001 vs. G3, NS vs. bupivacaine). Machine-learning models were trained and demonstrated satisfactory performance in predicting the time spent in recovery. Conclusions: In the context of endourological surgery, the time required for ambulation was shortest when using TIVA, while SPA with hyperbaric prilocaine provides the closest approximation to optimal anaesthesia.